Enhancing the development of intercultural communicative competence in business and study environments - Ozlem Yuges (Peoples' Friendship University of Russia (RUDN University), 2020)
In the world of international education and training, as well as international business, foreigners are increasingly coming to work, study and seek professional training at British universities and in company branches and affiliates around the world. Students and employees don't always find it easy to understand and communicate with their managers, teachers and lecturers, as many make little or no allowance for the language and cultural background of those they are managing, teaching and training. This paper explores the development of intercultural communicative competence in English language and cultural teacher training and management and asks how establishing effective and appropriate behaviour within intercultural communication promotes effective communication in teacher training programmes and in management training. It explores how the concept of intercultural sensitivity is integrated into intercultural communicative competence in training programmes and how it could facilitate the development of overall sensitivity. In doing so it identifies some of the enabling and hindering features that shape the development of intercultural communicative (or communication) competences in English Language and culture in training courses in management or university.